The relationship between pregnancy and temporomandibular disorder (TMD) through diagnostic criteria for temporomandibular disorders (DC/TMD) axis II evaluation: a case-control cross-sectional study - Giuseppe Minervini; Maria Maddalena Marrapodi; Marco La Verde; Aida Meto; Yuliia Siurkel; Marco Cicciù; Diana Russo (BMC, 2024)
Abstract Introduction This study focuses on temporomandibular disorders (TMDs), which affect the temporomandibular joint and related muscles and have multiple causes. Recent studies have examined the connection between menstrual cycles, estrogen levels, and TMDs, but results are inconsistent, highlighting the need for more research. The aim is to explore the prevalence of TMDs in pregnant women and consider how hormonal changes during pregnancy might influence these disorders. Methods In this cross-sectional case-control study, we compared 32 pregnant women with 35 non-pregnant women. We evaluated several TMD-related factors such as pain levels, chronic pain classification, scores on the Jaw Functional Limitation Scale-20 and Oral Behaviors Checklist, and psychological health. We used various statistical methods including descriptive statistics, chi-square tests, linear regression, and adjustments for multiple comparisons to analyze the data. Results Pregnant women showed different pain perceptions, generally reporting less pain and lower severity. Nonetheless, these differences were not uniform across all TMD-related measures. Linear regression did not find a consistent link between pregnancy and TMD scores, except for chronic pain grade, which was not significant after adjusting for multiple comparisons. There was a significant relationship between depression and TMD severity, emphasizing the need to consider mental health in TMD evaluations. Discussion The findings suggest that pregnancy is neither a risk nor a protective factor for TMD. Differences in pain perception, functional status, and psychological health were observed in pregnant women but were not consistent for all TMD-related aspects. The role of estrogen in TMJ health and TMD risk is complex and requires further study. The research highlights the necessity of including mental health, especially depression, in TMD assessments. More comprehensive research with larger sample sizes is essential to better understand the connections between pregnancy, TMD, and hormones, aiming to improve TMD management in pregnant women and others.